Sosialisasi Zero Waste Living Margo Mulyo “Menciptakan Lingkungan Sekolah Bersih dan Sehat” - Waladdin Panggabean; Gessy Rantrove Nainggolan; Nur Hafidah Rahman; Micky Andhreanto; Graciella Manope; Dewi Sekar Arningtias; Muhammad Rafli; Thalia Fitri Salsabila; Wita Saulina; Alfa Rizky Ramadhan; Syara Arini Putri (Nuras : Jurnal Pengabdian Kepada Masyarakat, 2026)
Waste management in the school environment remains a challenge in creating a clean and healthy learning environment. The lack of students' understanding of waste management and the health impacts of littering behavior is the background of this activity. The "Zero Waste Living Margo Mulyo: Creating a Clean and Healthy School Environment" program aims to improve the understanding of fourth grade students at SD Negeri 008 Balikpapan Barat regarding the 3R concept (Reduce, Reuse, Recycle), English vocabulary related to cleanliness, and the importance of maintaining environmental hygiene. The activity was carried out with a participatory-educational approach through material delivery, interactive discussions, and waste sorting practices. Data were collected through observation and documentation during the activity. The results of the activity showed an increase in students' understanding of the 3R concept, an increase in English vocabulary related to cleanliness, and an increase in awareness in maintaining the cleanliness and health of the school environment. This program shows that practice-based and interactive education is effective in instilling environmental awareness from an early age, while contributing to supporting sustainable development efforts in the elementary education environment.